Design, Build and Validation of a Low-Cost Programmable Battery Cycler. (6th December 2016) - Propp, Karsten; Fotouhi, Abbas; Knap, Vaclav; Auger, Daniel J
Abstract : The availability of laboratory grade equipment for battery tests is usually limited due to high costs of the hardware. Especially for lithium-sulfur (Li-S) batteries these experiments can be time intensive since the cells need to be precycled and are usually cycled with relatively low loads. To improve the availability of test hardware, this paper conducts a study to design and test a low cost solution for cycling and testing batteries for tasks that do not necessarily need the high precision of professional hardware. While the described solution is in principle independent of the cell chemistry, here it is specifically optimized to fit to Li-S batteries. To evaluate the accuracy of the presented battery cycler, the hardware is tested and compared with a professional Kepco bipolar power source. The results indicate the usefulness for application oriented battery tests with real life cycles, although inaccuracies occur in the current measurements.